IDENTIFIKASI JENIS TUMBUHAN FAMILY ZINGIBERACEAE DI KEBUN RAYA SRIWIJAYA KABUPATEN OGAN ILIR PROVINSI SUMATERA SELATAN - Hamidi Hamidi; Amin Nurokhman; Jhon Riswanda; Ummi Hiras Habisukan; Khalida Ulfa; Arif Yachya; Sri Maryani (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2022)
Zingiberaceae is a family of spice plants that are commonly found in the Sriwijaya Botanical Gardens, this type of plant is often used as medicine, cooking spices, ornamental plants and hair medicine. Families of Zingiberaceae are still not well identified. This study aims to determine the species of the Zingiberaceae families in the Sriwijaya Botanical Gardens. This research uses descriptive qualitative research and uses the method of exploring the location in the Kebun Raya Sriwijaya. The identification results obtained six species of plant species from the Zingiberaceae family, namely galangal: Alpinia galanga (L.) Wild., yellow turmeric: Curcuma longa L., kencur: Kaempferia galanga L., white turmeric: Curcuma zeodaria (Christem.) Roscoe., ginger white : Zingiber officinale var. amrum., and forest galangal : Alpinia malaccensis.